Utilization of Effluent Fish Farms in Cultivation Using Aquaponics - AKHILA G.L JASBEER K.T; Dr. Anu Varughese (Guide) (tavanur 2017 Department of Irrigation & Drainage Engineering)
Utilization of Effluent Fish Farms in Cultivation Using Aquaponics
Utilization of Effluent Fish Farms in Cultivation Using Aquaponics